Burnout Syndrome in Brazilian Medical Doctors: A Cross-Sectional Examination of Risk and Protective Factors - Becker, Natalia Dalla Costa; Carlos da Rocha, Adilson; Follador, Franciele Aní Caovilla; Wendt, Guilherme Welter; Ferreto, Lirane Elize Defante; Fortes, Paulo Nunes; Amorim, João Paulo Arruda (Frontiers in Health Services, 2021)
Objectives: This investigation sought to identify the prevalence of Burnout Syndrome (BS) among Brazilian medical doctors (BS) and the associations with risk factors and protective factors. Methods: Out of 206 registered MD from a medium-sized municipality, 121 were enrolled in this cross-sectional study. Convenience sampling was used. Based on Cohen’s f2, a power of 98% and a 0.05 alpha was achieved. MD responded to sociodemographic questions and to the Portuguese-version of the Maslach Burnout Inventory–Human Services Survey (MBI). Risk and protective factors linked with BS were examined with regression analyses. Results: The age of the participants ranged from 25 to 69 years (M=40.89; SD=10.13) and 73.6% were male. The prevalence of BS was 7.5%. Differential aspects were related to BS. For instance, while not reporting satisfaction with the institution (β=16.16, p<0.001) and not practicing physical exercise (β=7.39, p=0.014) were associated with higher scores in the BS composite score, those who did not intend to change their careers (β=-17.15, p<0.001) and participants who saw mental health specialists (β=-8.99, p=0.007) scored lower, accounting for nearly a half of the BS composite score (R2=46%). Conclusion: The prevalence of BS in this study falls within the range previously reported among healthcare professionals (i.e., 2.6 to 11.8%). Moreover, data suggested that commitment with the occupation and with the participant’s own mental health could boost reactions against the deleterious effects of the BS. In this sense, organizations can develop strategies for preventing BS, a process that is known to be chronic and, to some extent, preventable.